Protecting local heritage places : a guide for communities. - Australian Heritage Commission (Canberra : Australian Heritage Commission, 1998)
This guide contains information to help individuals and groups working locally to identify, conserve and protect heritage places. It has drawn together, through workshops and submissions from all over Australia, the current knowledge of how to identify and care for heritage places.
Introduction -- 1. Heritage places -- 2. Planning your approach -- 3. Heritage places and values -- 4. A heritage study -- 5. Collecting heritage information - 6. Conservation plans -- 7. Raising support for heritage conservation -- 8. Heritage protection for local authorities -- 9. Monitoring progress -- Resources -- Heritage organisations -- Criteria for the Register of the National Estate.
Includes index.
"This guide contains information to help individuals and groups working locally to identify, conserve and protect heritage places" p. 2.
Bibliography: p. 111-114.
Keywords: Cultural property -- Protection -- Australia; Historic sites -- Australia -- Conservation and restoration; Landscape protection -- Australia; Historic buildings -- Australia -- Conservation and restoration; Cultural heritage